إشكالية الشرعية الأجناسية لرحلة ابن حمادوش الجزائري - لعراب, وردة; حني, عبد اللطيف (University of El-oued, 2021)
الرحلة قديمة قدم الإنسان الذي فطن على الحل والترحال، فقد جاب كل أرجاء المعمورة مشاهدا ومعاينا وملاحظا، تحولت الرحلات مند القرن التاسع عشر الميلادي من قالب حركي انتقالي إلى قالب سردي مكتوب، اختلفت مضامينها فاختلفت أساليب كتابتها ،فاختلف النقاد في تصنيفها الأجناسي، ومن بين الرحلات التي استعصت على الانتساب النوعي "رحلة بن حمادوش الجزائري المسماة لسان المقال في النبأ عن النسب والحسب والحال" والتي نحاول في هاته الورقة البحثية أن نقف على الإشكالات التي طرحها النص محاولين أن نصنفها تحت شكلها الأجناسي الحقيقي الذي تدلي عليه معطيات المتن بصورة واضحة ومباشرة وقوفا عند المقومات الشكلية الموازية والمركزية التي تدلنا على ذلك. The journey is as old as the person who discerned traveling, as he traveled all over the globe as a viewer, a witness and an observer. From the nineteenth century AD, the journeys have transformed from a transitional dynamic template to a written narrative template that its contents differed, so its writing styles differed, and also critics disagreed in its gender classification. Among the trips that eluded specific affiliation we have the Journey of Ben Hammadoush Al-Jazaery called “ Lissan Elmaqal Fi Ennabaa 3an Enasab wa Elhassab wa Elhal” and in this paper we try to identify the problems raised by the text, trying to classify them under their true gender classification form, which is clearly and directly indicated by the data of the text standing at the parallel and central formal elements that indicate this.
مقال. مجلة القارئ للدراسات الأدبية والنقدية. مج04. ع.02. جامعة الوادي
Keywords: الرحلة ; ابن حمادوش ; التجنيس ; النص الموازي ; النص المركزي